2014
DOI: 10.1371/journal.pone.0107181
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Outcome of Severe Sepsis and Septic Shock in Intensive Care Units in Mainland China

Abstract: IntroductionInformation about sepsis in mainland China remains scarce and incomplete. The purpose of this study was to describe the epidemiology and outcome of severe sepsis and septic shock in mixed ICU in mainland China, as well as the independent predictors of mortality.MethodsWe performed a 2-month prospective, observational cohort study in 22 closed multi-disciplinary intensive care units (ICUs). All admissions into those ICUs during the study period were screened and patients with severe sepsis or septic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
150
6
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 176 publications
(169 citation statements)
references
References 33 publications
10
150
6
3
Order By: Relevance
“…Similar to these results, Zhou et al (7) showed that among patient with severe sepsis and septic shock, Gram-negative organisms ranked the highest (62.5%), followed by Grampositive organisms (14.5%) and fungi (2.2%), respectively. Since mainland China lacks the national investigation of the pathogen of sepsis, it may vary in different districts and ICU wards.…”
Section: Pathogensupporting
confidence: 57%
See 1 more Smart Citation
“…Similar to these results, Zhou et al (7) showed that among patient with severe sepsis and septic shock, Gram-negative organisms ranked the highest (62.5%), followed by Grampositive organisms (14.5%) and fungi (2.2%), respectively. Since mainland China lacks the national investigation of the pathogen of sepsis, it may vary in different districts and ICU wards.…”
Section: Pathogensupporting
confidence: 57%
“…Among the 3,665 patients admitted to ICU, 318 developed severe sepsis, i.e., 8.68% of the total population. Another prospective, observational cohort study conducted in 22 ICUs from July 2009 to August 2009 reported that among 1,297 patients enrolled, 484 (37.3%) developed severe sepsis and septic shock (7). Both of the studies used the American College of Chest Physicians/Society of Critical Care Medicine consensus criteria to define severe sepsis.…”
Section: Incidence Of Icu-treated Sepsismentioning
confidence: 99%
“…A recent meta‐analysis of RCTs reported that the survival benefit of anticoagulant therapy was observed only in sepsis patients with DIC, but not in those without DIC 10. Furthermore, although many epidemiological studies for sepsis have been carried out,11, 12, 13, 14, 15 epidemiological data regarding sepsis in Japan is limited 16, 17…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have described the epidemiology, risk factors, and outcomes of sepsis (1)(2)(3)(4) . However, why some patients recover from sepsis while others do not remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Between 6 and 54% of the patients admitted to ICUs have severe sepsis, and the mortality rate for these patients varies from 20 to 60%, which increases stepwise with increasing disease severity. Several studies have described the epidemiology, risk factors, and outcomes of sepsis, severe sepsis, and septic shock (1)(2)(3)(4) . However, why some patients recover from sepsis while others do not, remains unclear.…”
Section: Introductionmentioning
confidence: 99%